Cell-Based Approaches to the Engineering of Vascularized Bone Tissue - Rao, Rameshwar R. (2013)
This review summarizes recent efforts to create vascularized bone tissue in vitro and in vivo using cell-based therapy approaches. The treatment of large and recalcitrant bone wounds is a serious clinical problem, and in the United States approximately 10% of all fractures are complicated by delayed or non-union. Treatment approaches using growth factor and gene delivery have shown some promise, but results are variable and clinical complications have arisen. Cell-based therapies offer the potential to recapitulate key components of the bone healing cascade, which involves concomitant regeneration of vasculature and new bone tissue. For this reason, osteogenic and vasculogenic cell types have been combined in co-cultures to capitalize on the function of each cell type, and to promote heterotypic interactions. Experiments in both 2D and 3D systems have provided insight into the mechanisms by which osteogenic and vasculogenic cells interact to form vascularized bone, and these approaches have been translated to ectopic and orthotopic models in small animal studies. The knowledge generated by these studies will inform and facilitate the next generation of pre-clinical studies, which are needed to move cell-based orthopaedic repair strategies into the clinic. The science and application of cytotherapy for repair of large and ischemic bone defects is developing rapidly, and promises to provide new treatment methods for these challenging clinical problems.